Salmonella spp. among Food Handlers in the Dining Room at a Venezuelan University - Lisette Beatriz Sandrea Toledo; Eyilde Josefina Piña Reyes; América Paz Montes; Jennireth Ramírez; María Robertis; Daleine Romero; Yulisbeth Soto (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
The relationship between inadequate food handling and the production of gastrointestinal infections has been amply demonstrated, and a variety of organisms, including Salmonella, are associated with this transmission. The purpose of this research was to detect the prevalence of Salmonella in stool samples from food handlers who work in two dining rooms at the Zulia state university. Between April and July of 2009, 40 samples were cultured from stools of asymptomatic individuals of both sexes and different ages. Isolation, biochemical and serological identification were performed using conventional methodology. Tests for susceptibility to antimicrobial agents were done using the disk diffusion method, following criteria established by the CLSI. Of the total samples processed, four of them (10%) were positive for Salmonella 3, (75%) for serogroup B and 1 (25%) for serogroup E1. 50% of the strains were ampicillin resistant. The presence of Salmonella in the stools of food handlers is a major public health problem that should not go unnoticed due to its high infectivity and association with major outbreaks.